Environmental Fate of Two Organophosphorus Insecticides in Soil Microcosms under Mediterranean Conditions and Their Effect on Soil Microbial Communities. Issue 3 (3rd April 2019) - Ben Salem, Asma; Chaabane, Hanene; Caboni, Pierluigi; Angioni, Alberto; Salghi, Rachid; Fattouch, Sami
ABSTRACT: Assessing dissipation is an integral part of determining pesticide risk. The adsorption and dissipation characteristics of two model insecticides, chlorpyrifos (CHP) and dimethoate (DMT), in a Mediterranean soil were investigated in order to evaluate soil microbial toxicity and to study their soil bioavailability for the purpose of managing pesticide residue with potential bioremediation of contaminated soil. The aim of this study was also to define novel methods for assessing the ecotoxicity of CHP and DMT on microorganisms in the soil. Koc values ranged between 33420–91601 cm 3 /g and 129–184 cm 3 /g for CHP and DMT, respectively, indicating that the former is characterized by a strong adsorption affinity, whereas, the latter has a weaker one. In the dissipation study, the half-life ( T 1/2 ) of CHP in top soil was 11.55days; whereas, when dissipation was studied in the same soil sterilized, the half-life was 13.86 days, showing a relatively important abiotic degradation effect. For DMT, however, T 1/2 was 17.32 days and 13.86 days in sterilized soil and non-sterilized soil, respectively, illustrating partial biotic degradation. In terms of leaching behavior, the groundwater ubiquity scores calculated for CHP and DMT were 0.85 and 1.95, respectively, indicating that CHP is a non-leacher, while DMT can be considered a transition insecticide.